Effect of Musca domestic maggot polypeptide extract on HUVEC dysfunction induced by early-activated macrophages. (2nd April 2016) - Chu, Fujiang; Jin, Xiaobao; Ma, Hongyan; Lu, Xuemei; Zhu, Jiayong
Abstract: Context : Musca domestica Linn. maggot is a traditional Chinese medicine. In our previous studies, Musca domestica maggot protein-enriched fraction and polypeptide extract (molecular weight <30 kD) were found to reverse endothelial cell dysfunction in atherosclerotic lesions. Objective : This study determines whether and how M. domestica maggot polypeptide extract affects the dysfunction of human umbilical vein endothelial cells (HUVEC) induced by macrophages (Mϕ). Materials and methods : HUVEC and early-activated THP-1 Mϕ (incubated with LPS of 1 μg/ml for 2 h) were co-cultured in a Transwell system. The effects of Musca domestica maggot polypeptide extract (with increasing concentrations, i.e., 1.0, 2.5, 5.0, 10.0, 20.0, and 40.0 µg/ml) on the proliferation and migration HUVEC and their secretion of vascular endothelial growth factor (VEGF) were determined by flow cytometry, modified Boyden chamber assay, and enzyme-linked immunosorbent assay (ELISA) after incubation for 24 h. Results : Musca domestica maggot polypeptide extract decreased the proliferation of HUVEC in a concentration-dependent manner, with a 50% effective concentration (EC50 ) of 22.16 ± 1.48 µg/ml, and effectively inhibited HUVEC migration (EC50 = 35.15 ± 2.03 µg/ml) and VEGF secretion (EC50 = 28.64 ± 1.29 µg/ml). Discussion and conclusion : Musca domestica maggot polypeptide extract can inhibit the dysfunction of HUVEC induced by early-activated THP-1 Mϕ.